Estrutura da fauna bentônica de duas praias do norte do Espírito Santo - Teixeira, Bruna Adenalian Coelho (2016)
This study characterized the benthic fauna of two northern beaches of the Espírito Santo. two samples were taken throughout the year , in Urssuquara, São Mateus (19°03’45,2”S e 39°43’28,9” O) was december/2014 e july/2015; and in Degredo, Linhares (19°24’47,1”S e 39°42’37,4”O) was january/2015 e setember/2015. Sampling always occurred in low tide of sizigia, it was made a total of 27 samples for each variable (macrofauna, meiofauna and sediment). The samples macrofaunal and particle size were taken with a PVC sampler and the meiofaunal with a syringe, quantified and identified in the laboratory. The uni- and multi-factor analysis showed significant differences in the benthic fauna components between the substrates (p< 0.05). The diversity of macrofauna was lower in subtidal Beach Urussuquara. The density, richness and diversity of meiofauna were higher in the subtidal. And of the Nematoda (genres) density and richness were higher in the subtidal. The most abundant organisms were the genus Polychaeta Polygordius in macrofauna and the gender Nematoda Daptonema. In Degredo, macrofauna higher density, richness and evenness in the mid-upper. The density of meiofauna was higher in the mid-upper; the richness, evenness and diversity were higher in the midlower. Nematofauna had no significant results. The most abundant organisms were the genus Polychaeta Novaquesta in macrofauna and the gender Nematoda Microlaimus. Multivariate analyzes showed higher mid-upper as the different track from the others. The characterization of the benthic community and the issues discussed are of paramount importance to assist in conservation actions.